Retrospective Analysis of Extra-Pelvic Injuries Verified at the First Admission of Cats With Pelvic Fractures - de Morais, Caroline Molon [UNESP] (2023)
This retrospective study aimed to identify the common extra-pelvic injuries at the first admission at the hospital of cats with pelvic fractures. The medical records and radiographs were assessed. Seventy-three cats with pelvic fractures were identified, of which 41 were associated with extra-pelvic injuries. Of the 41 animals with extra-pelvic injuries, 21 were females and 20 were males. Motor vehicle trauma represented 56.09% of the pelvic fracture cause. Injuries to the appendicular skeleton included femur (n=12), tibia (n=1), lateral malleolus (n=1) and olecranon (n=1) fractures, and unilateral hip luxation (n=4). In the axial skeleton, mandibular condyle fracture (n=1), fracture of lumbar vertebrae (n=1), fracture and/or luxation of the coccygeal vertebrae (n=3), and luxation between S3 and the first coccygeal vertebra (n=3) were detected. Sacrum or sacroiliac fractures were detected in six cases. Sacroiliac luxation was verified in 22 cats unilaterally (n=15) and bilaterally (n=7). Respiratory tract lesions were pulmonary contusion (n=2), pneumothorax (n=2), and diaphragmatic hernia (n=1). Lesions of the urinary system organs included bladder rupture (n=3) and bladder entrapment in the hernia (n=1). In the integumentary system, there was one case of cutaneous laceration and one of subcutaneous emphysema. Traumatic hernias of the abdominal wall were found in five cats. Nervous system lesions included traumatic brain injury (n=2) and spinal cord injury (n=1). Two cats presented with constipation. Two animals died, and two were euthanized due to the severity of the injuries. In conclusion, the extra-pelvic injuries at admission were more frequent in the appendicular skeleton, mainly represented by femur fractures.